Classification criteria and treatment modalities in primary Sjögren's syndrome. (April 2014) - Fazaa, Alia; Bourcier, Tristan; Chatelus, Emmanuel; Sordet, Christelle; Theulin, Arnaud; Sibilia, Jean; Gottenberg, Jacques-Eric
<x xml:space="preserve">Abstract</x> Primary Sjögren's syndrome is a systemic autoimmune disease, characterized by a lymphocytic exocrinopathy. Oral and ocular dryness, asthenia and pain represent hallmarks of the disease. Systemic manifestations concern a third of patients, including lymphoma in 5% of the patients. The American European Consensus Group classification criteria have been used in current practice and clinical trials since 2002. New classification criteria were recently proposed by the American Congress of Rheumatology. A group of international experts are currently working to reach a new consensus between the American European Consensus Group classification criteria and the American Congress of Rheumatology proposal for disease classification. In addition, international consensus disease activity scores were recently established. Regarding treatment modalities, symptomatic treatments remain the cornerstone of therapy in pSS, but new biologic treatments are currently evaluated.